2006
DOI: 10.25249/0375-7536.2006363535549
|View full text |Cite
|
Sign up to set email alerts
|

La Dorsal Asunción - Río Grande: Un Altofondo Regional Entre Las Cuencas Paraná (Brasil, Paraguay Y Uruguay) Y Chacoparanaense (Argentina)

Abstract: Rcvista Brasilcira de GcocicnciasEduardo A. Resumen La Dorsal Asu ncio n -Rio G rande (DARG) cs un accidcme tcctonico de primcra magnitud que con stituyo un a ltofondo regional rcspon sable de la com part imc ntalizacion de la scdirncntacion post-Permico-Triasico de las cuencas Parana (Brasil, Paragu ay y Urug uay ) y de 1' 1 Llanura Ch acoparancnse (A rge nt ina). El ext reme septentrional de la DA RG. ell Paraguay. csta repr osentado pm cI A lto Asuncio n materiali zado por una vcn tana del busam cnto cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
3
6
0
Order By: Relevance
“…In particular, during the Mesozoic, it seems to have been a structural block with topographic expression, controlling the thinning of the GAS units and avoiding basaltic flow accumulation. This would be consistent with the comments made by previous authors about the DARG evolution, Williams (1995) and Rossello et al (2006), whom confirmed the gradual tectonic uplift of DARG from Carboniferous. This NW structuring, coincident with the axial trace of the DARG, has interrupted the continuity of Corrientes and Curuzú grabens towards the NE, and those depocenters outline their continuity in the northeast of Corrientes province and all around Misiones province.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In particular, during the Mesozoic, it seems to have been a structural block with topographic expression, controlling the thinning of the GAS units and avoiding basaltic flow accumulation. This would be consistent with the comments made by previous authors about the DARG evolution, Williams (1995) and Rossello et al (2006), whom confirmed the gradual tectonic uplift of DARG from Carboniferous. This NW structuring, coincident with the axial trace of the DARG, has interrupted the continuity of Corrientes and Curuzú grabens towards the NE, and those depocenters outline their continuity in the northeast of Corrientes province and all around Misiones province.…”
Section: Resultssupporting
confidence: 92%
“…Its result shows a basement compartmentalized in structural blocks separated by large faults which cross all the volcano-sedimentary sequence. Indeed, they demonstrated that the central-west region of Corrientes shows the least thickness of basalts coinciding with the axial trace of the Dorsal Asunci on-Rio Grande (DARG) just as the GAS sediments are thinner such as suggested in regional maps by Gastmans et al (2012), corroborating this structure in the terms described by Rossello et al (2006).…”
Section: Geological Background Of Corrientessupporting
confidence: 65%
See 1 more Smart Citation
“…Transmissivity (and for that matter hydraulic conductivity) is one of many aquifer parameters that vary with the scale of measurement. This issue is well documented in the literature (Sánchez-Vila et al, 1996;Nilsson et al, 2001). An in-depth analysis of this topic is well beyond the scope of this work.…”
Section: Hydraulic Conductivitymentioning
confidence: 73%
“…The Río de la Plata Craton (RP) is located in southeastern South America (Figure 3a), covering the province of Buenos Aires in Argentina, most of the territory of Uruguay, and southern Brazil. A large part of the craton is overlayed by Phanerozoic sediments, forming the Chaco-Paranaense basin (e.g., Rossello et al, 2006), which makes it difficult to establish the actual extension of the craton (Dragone et al, 2017;Oyhantçabal et al, 2010;Rapela et al, 2007;2011;Santos et al, 2017). As a fact, the Precambrian rocks are exposed only in its eastern and southern parts (Figure 3).…”
Section: Río De La Plata Cratonmentioning
confidence: 99%